Is It Inefficient Investment that Causes the Diversification Discount? - Whited, Toni M. (Journal of Finance, 2001)
ABSTRACT Diversified conglomerates are valued less than matched portfolios of pure‐play firms. Recent studies find that this diversification discount results from conglomerates' inefficient allocation of capital expenditures across divisions. Much of this work uses Tobin's q as a proxy for investment opportunities, therefore hypothesizing that q is a good proxy. This paper treats measurement error in q . Using a measurement‐error consistent estimator on the sorts regressions in the literature, I find no evidence of inefficient allocation of investment. The results in the literature appear to be artifacts of measurement error and of the correlation between investment opportunities and liquidity.